A Feasibility study on AEGIS sidearms in 0.45 caliber - Caday, Ma. Odette (College of Engineering, 1998)
To be registered under the Aegis trademark, the Aegis Model 153 in 0.45 caliber will be a new firearm to be introduced in the market. The model 153 patterned after the famous 1911 design which is characterized by simple and generic parts. among several improvements, the Model 153 sports a light combat hammer, serration on the front end of the slide, and better safety features which is a combination of the safety lock, grip safety, disconnector safety and an inertia firing pin. The Model 153 has an overall length of 8.5 inches, an overall height of 5.5 inches and weighs 39 ounces when empty. The project aims to sell a constant volume of 6,100 units annually during the first five years of production, for an initial market share of 15%. This level is equivalent to the sales volume previously maintained by the Arms Corporation of the Philippines (ARMSCOR) before it suspended its 0.45 caliber production in early 1998. To further stimulate demand and attract potential buyers, a modest promotional and advertising campaign will be launched. This is composed mostly of printed advertisements in major newspapers and magazines, distribution of posters and brochures to firearm dealers nationwide, participation in gun shows and partially sponsoring a team of sports shooters. All of these will amount to Php 1,497,000 for the first year. The production processes involved are very simple. It is composed of surface machining, bluing or finishing and assembly. There will be an average of 25 working days in a month and one 7.5-hour shift per working day. Production will be at 90.9% of capacity, which is at 510 units each month. 2 milling machines, one grinder and two buffers are the major equipment to be used. 9 workers will be manning the production floor and 5 workers will be assigned to other tasks such as quality inspection and delivery.. the entire plant will occupy a total floor area of 500 m² and will be situated in a 700 m² lot in Magat Salamat street, SSS Village, Marikina. The total fixed investment, with one year working capital plus 10% contingency allowance is estimated at PhP 69,938,435.17. A detailed monthly cash flow projection fro the first year showed that 6months working capital is more than sufficient to launch the project until it is self-sustaining, lowering the required investment to PhP 31,443,738,87. 25% of this amount will be loaned through, Security Bank, a commercial bank, with annual loan payments for a 7-year long term-loan at 17.8% interest. The remaining PhP 23,582,804.15 will be raised through equity. Cash flow projections showed that the investment will be completely recovered in approximately 3 years and 4 months, with a 69% internal rate of return. The project will be established as a corporation, which will be formally registered as Aegis Sidearm Manufacturing Corporation. Aside from the 14 production workers, 18 more employes will compose the office and support staff. The entry of Aegis into the local industry will basically reduce the demand for foreign-made firearms, pay the government an average of PhP 11 million annually, 32 more employment opportunities and a possible reduction of the local crime rate induced by an increasing armed populace. With all these established facts and figures, the establishment of a 0.45 caliber manufacturing company is an economically feasible and attractive business venture.